Biochemical indicators and course of dermatosis in children with psoriasis depending on the body mass index - Murzina, Elvina (ScienceRise: Medical Science, 2020)
The aim. To study the effect of increased body weight in children with psoriasis on the indicators of the biochemical profile and the severity of the pathological process. Materials and methods. The indicators of the biochemical profile were studied in 108 children, namely: the level of total protein, total bilirubin, cholesterol, liver enzymes (ALT, AST, GGT), triglycerides and low density lipoproteins, creatinine, urea, uric acid (UA), depending on the mass index body (BMI). The research materials were statistically processed using parametric analysis methods using the STATISTICA 13.3 software (developed by StatSoft. Inc). Results. Lipid profile indices both in the group of children with normal BMI and in the group of children with increased BMI are within the reference values. Statistically significant differences were found between the average GGT level in the group of children with increased BMI compared with the indicators in the group of children with normal BMI and indicators in the children of the control group. Also, in children with increased BMI, the average UA level is statistically significant higher than in children of the control group and has direct moderate and significant correlations with indices of the severity of the pathological process. In children with increased BMI, psoriasis severity indices correlate with BMI: PGA (r=0.51, p<0,01) BSA (r=0.48, p<0,01), PASI at the beginning of treatment (r=0.41, p<0,05) and PASI at the end of treatment (r=0.67, p<0.001) and percentage of excess body weight: BSA (r=0.34, p<0,05), PASI at the end of treatment (r=0.67, p<0.001). In children with normal BMI, such correlations were not found